Analisis Pengaruh Work-Life Balance dan Hybrid System terhadap Produktivitas Kerja - Jeah Yespy Juniarti; Yanti Pasmawati; Septa Hardini; M. Kumroni Makmuri (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
This study aims to analyze the effect of work-life balance and hybrid systems on employee work productivity. The background of this research is based on the phenomenon of changes in work systems after the pandemic and the increasing need for work-life balance. A quantitative approach was employed using a survey method involving 228 respondents working under a hybrid system. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that work-life balance and the hybrid system have a significant effect both partially and simultaneously on work productivity. The t-test results show significant values for both variables (X1 and X2), while the F-test demonstrates a strong simultaneous influence on the dependent variable. The coefficient of determination (R²) value of 0.453 indicates that 45.3% of the variability in work productivity can be explained by these two variables. The study concludes that implementing good work-life balance and a flexible hybrid system can enhance employee work effectiveness and efficiency. These findings are expected to serve as input for companies in formulating work policies that support sustainable well-being and productivity.